2002
DOI: 10.2466/pms.2002.95.2.507
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Tests of Attention and Performance on Grooved and Purdue Pegboards in Normal Subjects

Abstract: This study investigated the relation between tests of manual dexterity and attentional functions with 49 normal, right-handed medical students (26 women, 23 men, ages 19-30 years) who were assessed with a Purdue Pegboard Test, Grooved Pegboard Test, and a Test for Attentional Performance, comprising measures of tonic and phasic alertness and divided attention. Weak to moderately high partial correlations controlling for finger size were obtained between pegboard test performance of the left hand and phasic ale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Some studies found that women perform noticeably faster than men (Bryden & Roy, 2005;Polubinski & Melamed, 1986;Van Wijk, 2012), and greater inter-manual differences for females compared to males were reported (Thompson, Heaton, Matthews, & Grant, 1987). One study found significant gender differences for the dominant hand (DH) only (Schmidt, Oliveira, Rocha, & Abreu-Villaca, 2000), while another did not find any significant gender difference (Strenge, Niederberger, & Seelhorst, 2002). A review of six studies (N = 2382) by Mitrushina et al (2005) found that women outperformed men by 3.8 and 3.9 s for DH and non-dominant hand (NDH), respectively.…”
mentioning
confidence: 88%
“…Some studies found that women perform noticeably faster than men (Bryden & Roy, 2005;Polubinski & Melamed, 1986;Van Wijk, 2012), and greater inter-manual differences for females compared to males were reported (Thompson, Heaton, Matthews, & Grant, 1987). One study found significant gender differences for the dominant hand (DH) only (Schmidt, Oliveira, Rocha, & Abreu-Villaca, 2000), while another did not find any significant gender difference (Strenge, Niederberger, & Seelhorst, 2002). A review of six studies (N = 2382) by Mitrushina et al (2005) found that women outperformed men by 3.8 and 3.9 s for DH and non-dominant hand (NDH), respectively.…”
mentioning
confidence: 88%
“…Also, in the results of the present pursuit rotor test, the means improved at every trial until the 6th trial. This was different from the results of the pegboard test and coordinated exertion of force test using the same upper limbs (Nagasawa and Demura, 2002;Strenge et al, 2002). Seven to ten trials may be needed to obtain stabilized measurements.…”
Section: Discussionmentioning
confidence: 96%
“…Strenge et al (2002) examined the relationship between concentration and pegboard tests using healthy subjects, and reported that there were significant correlations. The pursuit rotor test has been mainly used to identify learning retention.…”
Section: Introductionmentioning
confidence: 99%
“…In the GP, there are 25 slotted holes arranged in a 5 X 5 square, and each is angled in a different direction (Lezak, 1983). In the PP, there are 50 slots arranged into two vertical columns, each consisting of 25 slots (Strenge, Niederberger, & Seelhorst, 2002). In both tasks, the patient is timed while inserting the pegs into the holes using both the dominant and non-dominant hand.…”
Section: Used the Groovedmentioning
confidence: 99%
“…In both tasks, the patient is timed while inserting the pegs into the holes using both the dominant and non-dominant hand. In the PP, the participant is also tested using both hands together to insert the pegs (Lezak, 1983;Strenge et al, 2002).…”
Section: Used the Groovedmentioning
confidence: 99%